KKN Reguler: Inovasi Digital untuk UMKM: Meningkatkan Eksposur dan Penjualan Anyaman Daun Pandan Melalui Daya Tarik Produk di Desa Wonorejo - Vito Qobul Choliek; Wiwit Indriati; Khansa Syahla Khairunnisa; Aas Hoeriyah; Oktaviola Nur Cahya; Ananda Raihan Dwi Saputra; Elis Dhia Sidqiya; Chaterine Nur Haliza; Imelda Wijaya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Kuliah Kerja Nyata (KKN) program in Wonorejo Village, Karanganyar District, Kebumen Regency, aims to bridge academic theory with community practice through the preservation of pandan leaf weaving crafts and the strengthening of local SMEs. This program involves students from Universitas Muhammadiyah Purwokerto for 32 days, focusing on increasing youth interest in traditional crafts and innovating product packaging. Methods employed include observation, field research, and training. Results indicate a decline in young artisans and a need for innovative packaging designs to improve product marketing. Social learning and innovation theories are used to encourage youth participation and enhance product appeal. The program faces challenges in attracting youth interest and the need for appropriate training. In conclusion, KKN successfully applies social and economic theories to address local issues, resulting in social changes that include economic development, skill enhancement, and the creation of a sustainable community.